Viability of Hand and Wrist Photogoniometry. (May 2018) - Meals, Clifton G.; Saunders, Rebecca J.; Desale, Sameer; Means, Kenneth R.
Background: No goniometric technique is both maximally convenient and completely accurate, although photogoniometry (ie, picture taking to facilitate digital angle measurement) shows promise in this regard. Our purpose was to test the feasibility and reliability of a photogoniometric protocol designed to measure wrist and digit range of motion in general.Methods: Two independent observers examined a sample of joints in both normal and abnormal hands according to a photogoniometric protocol. Interrater and intrarater correlation were calculated, and these measurements were compared with measurements made by a third independent examiner with a manual goniometer.Results: The photo-based measurements were reliable within and between observers; however, only a minority of these measurements were in agreement with manually collected values.Conclusions: At present, photogoniometry is not an acceptable alternative to manual goniometry for determining wrist and digit range of motion in general. Joint-specific photogoniometry should be the subject of future study, as should relevant imaging and software technology.